Digital Transformation Of Accounting And Its Impact On The Efficiency Of Accounting Registration Under The Government Accounting System, An Applied Study In The General Directorate Of Education In Najaf Governorate - Neamah Obaid ALabdaly, Mitham; Salih Edan, Thamir (Iraqi Journal for Administrative Sciences, 2024)
The research aims to test the impact of digital transformation represented by (computerized accounting) on ​​the efficiency of accounting registration. Although the Iraqi government adopted the e-governance project, it did not take serious steps to implement this project. The traditional method of conducting business based on manual effort is still prevalent in government economic units in general and the General Directorate of Education in the Najaf Governorate in particular. Accounting registration in the General Directorate of Education in Najaf Governorate is still based on paper accounting, despite the difficulties that accompany the adoption of paper accounting records as a mechanism for recording accounting operations. The most important conclusions reached by the research are that digital transformation contributes to increasing the efficiency of accounting registration by increasing the accuracy and ease of processing data. Digital transformation also contributes to reducing the time and effort required to perform tasks and contributes to developing the human capital of the economic unit.